2022
DOI: 10.1186/s12938-022-01051-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of bone marrow on the mechanical properties of trabecular bone: a systematic review

Abstract: Background Accurate evaluation of the mechanical properties of trabecular bone is important, in which the internal bone marrow plays an important role. The aim of this systematic review is to investigate the roles of bone marrow on the mechanical properties of trabecular bone to better support clinical work and laboratory research. Methods A systematic review of the literature published up to June 2022 regarding the role of bone marrow on the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Numerical simulations published by Dalstra and Huiskes [10] and Linstrom et al [11] have demonstrated that material parameters can be site-dependent due to specific load-bearing areas relating to Wolff's law [12]. Comparative studies [13,14] have shown that variability in material parameters can be pronounced and is strongly dependent on the location and type of harvesting for both bony and soft tissue structures [6,[15][16][17][18]. A previous study addressed the relevance of standardization of preparation and storage of biomechanical specimens under the aspect of reproducibility [19].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations published by Dalstra and Huiskes [10] and Linstrom et al [11] have demonstrated that material parameters can be site-dependent due to specific load-bearing areas relating to Wolff's law [12]. Comparative studies [13,14] have shown that variability in material parameters can be pronounced and is strongly dependent on the location and type of harvesting for both bony and soft tissue structures [6,[15][16][17][18]. A previous study addressed the relevance of standardization of preparation and storage of biomechanical specimens under the aspect of reproducibility [19].…”
Section: Introductionmentioning
confidence: 99%